Education For Economic Empowerment: A Multidisciplinary Approach In Management, Finance, Social Science, And Marketing Perspectives - Vinayagam, Dr. A; Jaisal, Dr. Manish Kumar; Maheswaran, Dr. V. Mani; Garg, Akansh (Migration Letters, 2024)
In today’s rapidly evolving global economy, achieving economic empowerment is paramount for individuals and communities to thrive. To address this multifaceted challenge, a multidisciplinary approach integrating perspectives from management, finance, social science, and marketing is essential. Management principles provide frameworks for effective resource allocation, organizational structuring, and strategic planning, enabling individuals to navigate complex economic environments. Finance offers insights into investment strategies, risk management, and financial literacy, empowering individuals to make informed decisions about wealth creation and management. Social science perspectives shed light on the socio-economic factors influencing economic empowerment, such as access to education, healthcare, and social support systems. Understanding these dynami[1]cs is crucial for designing inclusive policies and programs that uplift marginalized communities. Moreover, marketing plays a pivotal role in shaping consumer behavior, market trends, and product development. Leveraging marketing insights can enhance economic opportunities by identifying niche markets, fostering entrepreneurship, and promoting inclusive economic growth. By integrating these diverse perspectives, education for economic empowerment can equip individuals with the knowledge, skills, and resources needed to overcome barriers, seize opportunities, and achieve sustainable economic independence. This holistic approach not only fosters individual prosperity but also contributes to the overall socio-economic development of communities and nations. This paper investigates the nexus between education and economic empowerment, drawing on perspectives from management, finance, social science, and marketing disciplines. Applying a multidisciplinary perspective, the theme of education for the eradication of poverty is analyzed in ten bubbles, the best educational strategies exposed and recommendations for decision-makers and practitioners put forward. Our study conveys the impact of education on socioeconomic progress and the improvement of lives all over the world, through holistic development.